Healthcare Resource Use and Quality of Life Associated with Cognitive Impairment Among Patients with Schizophrenia. (April 2022) - Kadakia, Aditi; Fan, Qi; Fan, Angela; Shepherd, Jason; Bailey, Hollie; Dembek, Carole; Williams, Rhys
Abstract: Objectives: To investigate the association between cognitive impairment and hospitalizations, quality of life and satisfaction with life among patients with schizophrenia. Methods: A point-in-time survey was conducted between July and October 2019 via the Adelphi Schizophrenia Disease Specific Programme across the United States of America. Patients were stratified as mild or severe based on the level of cognitive impairment reported by their psychiatrist (normal, mild = mild; moderate, severe, very severe = severe). Multiple regression analysis was used to model the association between cognitive impairment and outcomes, adjusting for baseline characteristics. Results: Data were provided by 124 psychiatrists for 651 mildly and 484 severely impaired patients with schizophrenia; PSCs were completed by 349 mildly and 206 severely impaired patients. Severe cognitive impairment was associated with increased odds of hospitalization due to schizophrenia relapse since diagnosis (2.10 odds ratio [OR], P  = .004) and within 12 months (1.95 OR, P  < .001) compared to mild impairment. Moreover, patients with severe cognitive impairment had poorer quality of life according to the EuroQoL 5-dimension (EQ-5D) Health Index (−0.085 coefficient, P  < .001) and EQ-5D Visual Analogue Scale (−6.24 coefficient, P  = .041) compared to patients with mild cognitive impairment. Severe cognitive impairment was also associated with lower overall life satisfaction according to the Quality-of-Life Enjoyment and Satisfaction Questionnaire (−8.13 coefficient, P  = .006) compared to mild cognitive impairment. Conclusion: Schizophrenia patients with severe cognitive impairment had more hospitalizations due to relapse than patients with mild cognitive impairment. Additionally, patients with severe cognitive impairment had significantly lower quality of life and overall satisfaction with life compared to patients with mild cognitive impairment. Funding: Sunovion Pharmaceuticals